2015
DOI: 10.1007/s00261-015-0388-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon presentations of common pancreatic neoplasms: a pictorial essay

Abstract: Pancreatic neoplasms are a wide group of solid and cystic lesions with different and often characteristic imaging features, clinical presentations, and management. Among solid tumors, ductal adenocarcinoma is the most common: it arises from exocrine pancreas, comprises about 90% of all pancreatic neoplasms, and generally has a bad prognosis; its therapeutic management must be multidisciplinary, involving surgeons, oncologists, gastroenterologists, radiologists, and radiotherapists. The second most common solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Solid pseudopapillary tumors,[ 39 40 ] cystic neuroendocrine neoplasms of the pancreas,[ 41 42 43 44 ] acinar cell neoplasms,[ 45 ] and pancreatic adenocarcinomas (adenosquamous and/or anaplastic carcinoma)[ 46 ] can occasionally appear as cystic masses.…”
Section: True Cysts — Nonneoplasmsmentioning
confidence: 99%
“…Solid pseudopapillary tumors,[ 39 40 ] cystic neuroendocrine neoplasms of the pancreas,[ 41 42 43 44 ] acinar cell neoplasms,[ 45 ] and pancreatic adenocarcinomas (adenosquamous and/or anaplastic carcinoma)[ 46 ] can occasionally appear as cystic masses.…”
Section: True Cysts — Nonneoplasmsmentioning
confidence: 99%
“…DWI may help in the detection of P-NENS, especially for localizing non-hypervascular neoplasms [ 21 ]. It has been reported that P-NENs with different grades of differentiation can be distinguished evaluating ADC maps: poor-differentiated P-NENs have significantly lower mean ADC values compared to normal pancreatic tissue and to well-differentiated pancreatic neuroendocrine tumors [ 22 – 24 ]. DWI MR could predict pancreatic neuroendocrine tumor grade, as reported in the literature, playing a role in tumor prognostic stratification at the beginning of the clinical history of the patient [ 25 ].…”
Section: Typical Imaging Presentationsmentioning
confidence: 99%
“…P-NENs could show atypical behavior. The most common atypical presentations are the hypoenhancing pattern, the intravessels growth, the intraductal growth, and the cystic and calcified variants [ 22 ].…”
Section: Atypical Imaging Presentations and Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncommon presentations of IPMNs include the dilatation of the entire ductal system (pan-ductal-ectasia), invasion or fistulation of adjacent structures such as bowel loops or common bile duct, and rarely intra-abdominal perforation resulting in pseudomyxoma peritonei [43]. …”
Section: Common Pancreatic Cystic Neoplasmsmentioning
confidence: 99%